1976
DOI: 10.1051/jphyscol:1976777
|View full text |Cite
|
Sign up to set email alerts
|

Point Defect Parameters for Calcium Fluoride From Ionic Conductivity Measurements at Low Temperatures

Abstract: Rbsum6. -La conductivite des cristaux, purs et dopes au sodium, a kt6 mesurke B des temperatures allant jusqu'a 1 125 K, en evitant toute reaction chimique entre le fluorure de calcium et la vapeur d'eau residuelle, ou l'oxygkne. Les donnees ont kt6 analysks a l'aide de techniques des moindres carres non lineaires pour obtenir des valeurs numeriques des paramktres gouvernant la formation et la migration des dkfauts. Ces resultats sont comparQ avec des travaux experimentaux et theoriques anttrieurs, et montrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Ure indicated that his analysis of the conductivity data could lead to substantial errors in the values for the interstitial mobility, since a correction had to be made for conduction of fluoride interstitials along grain boundaries. A detailed study and analysis of the conductivity of CaF 2 appeared more recently, and revealed numerical values for defect parameters that are consistent with the data reported by Bollmann and co-workers [23].…”
Section: Cafsupporting
confidence: 72%
“…Ure indicated that his analysis of the conductivity data could lead to substantial errors in the values for the interstitial mobility, since a correction had to be made for conduction of fluoride interstitials along grain boundaries. A detailed study and analysis of the conductivity of CaF 2 appeared more recently, and revealed numerical values for defect parameters that are consistent with the data reported by Bollmann and co-workers [23].…”
Section: Cafsupporting
confidence: 72%
“…It is to be emphasized that the activation energy, 0.502 el7, is similar t o that for "free"-vacancy migration in calcium fluoride, which has been found to lie in the range 0.35 to 0.55 eV [2].…”
Section: It Was Found That For Each Temperature the Most Probable Relmentioning
confidence: 97%
“…cm -2 ) t/(eV) E F (eV) AE" (eV) AE,-(eV) Table 3. Perfect-crystal and anion-defect quantities (e 0 , e x static and high-frequency dielectric constants, c, y elastic constants, U cohesive energy per unit cell, relative to free ions, E F Frenkel formation energy, A£ v , AE, vacancy and interstitial migration energies, calculated from the potential model and and compared with the experimental results listed by Catlow and Norgett (1973) and by Jacobs and Ong (1976). …”
Section: Interaction Modelsmentioning
confidence: 99%